Pemberdayaan Masyarakat melalui Keterampilan Lokal dalam Pengembangan Ekonomi Kreatif dan Pariwisata di Kampung Pelangi Semarang - Wawuru, Jessrik Wita; Aryaningtyas, Aurilia Triani (Universitas Batanghari Jambi, 2024)
This study aimed to explore the role of local skills in community empowerment in Kampung Pelangi Semarang, a tourist destination that has developed a community-based creative economy. The findings revealed that local skills such as handicrafts, painting, traditional performing arts, and culinary arts play a central role in economically empowering the community and promoting local cultural identity. Effective empowerment strategies included skills training, business assistance, and the formation of creative business groups that facilitated collaboration and product marketing. However, key challenges faced were limited access to capital, limited marketing reach, competition with mass products, and a lack of appreciation for the uniqueness of local skill products. To overcome these challenges, this study recommends strong synergy and collaboration among the community, government, academics, and the private sector. The government plays a role in providing access to capital, training, and business assistance. The private sector can be involved in expanding market opportunities. Academics can provide assistance and further studies. Additionally, local leadership and efforts to promote appreciation for local skills are crucial. To ensure sustainability, economic, social, and environmental aspects need to be considered in developing local skills. Product diversification, value addition, equal participation, and environmentally friendly production practices need to be adopted. The limitation of this study is its focus on a single case study in Kampung Pelangi Semarang, thus limiting the generalization of findings. Additionally, this study did not explore the environmental impact of creative economy and tourism activities in depth.